STRATEGI PEMASARAN JAMUR TIRAM DI DESA SIMPANG LIMBUR MERANGIN KECAMATAN PAMENANG BARAT KABUPATEN MERANGIN PROVINSI JAMBI MENURUT EKONOMI SYARIAH - Okta Citra Ulya; A.A Miftah; G.W.I. Awal Habibah (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
This research aims to find out what the Marketing Strategy for Oyster Mushrooms is in Simpang Limbur Village, Merangin, West Pamenang District, Merangin Regency, Jambi Province, according to Sharia Economics, as well as knowing the Sharia economic review of the Marketing Strategy for Oyster Mushrooms in Simpang Limbur Village, Merangin, West Pamenang District, Merangin Regency, Jambi Province. This research is a field research study by exploring data sourced from the research location in the oyster mushroom business in Simpang Limbur Merangin village, West Pamenang sub-district, Merangin district, Jambi province. The subjects in this research were 5 owners, employees and consumers of the oyster mushroom business in Simpang Limbur Merangin Village, with a sampling technique using the total sampling method. Data collection techniques through observation, interviews and documentation. The data analysis technique used in this research is qualitative descriptive of primary and secondary data. The results of this research show that the marketing strategy implemented by the oyster mushroom business in Simpang Limbur Merangin Village to increase sales is adequate, by implementing a product, price, place, promotion marketing mix system. The products marketed are of good quality and use quality production materials. The prices are set in accordance with the quality of the goods and maintain price stability, meaning giving the same price to each customer without any differences between one another. Strategic business location and easy to reach consumers. Promotions implemented using 2 methods, namely: personal selling, and product discounts have been carried out well and effectively. Competent human resources according to their fields and expertise. In the production process, quality materials are used, and the physical evidence shown in the cultivation of oyster mushrooms in the marketing process is in accordance with market demand. In the review of Sharia Economics, it is concluded that the marketing strategy implemented is in accordance with sharia principles. The products offered are halal, the pricing is not burdensome for both parties, the business location is very strategic and easy for consumers to reach and the promotions are carried out honestly, correctly and with a humble attitude in serving consumers with full sincerity and without prejudice or bad-mouthing. bad luck to other oyster mushroom farmers. Human resources who understand Islamic values. A process that does not deviate from Islamic teachings, and in terms of physical form does not show the luxury of the place, and provides convenience and comfort facilities for consumers.